Ensino de física sob o enfoque CTS: relações entre as leis da física e a educação para o trânsito - Saturnino, Vinícius Francisco Batista [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
The present work has as its main goal to point out the possibility of developing, in physics classes, the physical concepts associated with traffic education, through the Science- Technology-Society (STS) approach. Firstly, we tried to emphasize how the STS social movement emerged, at the global and national level, and how the teaching of science has been affected by this line of thought. Next, we sought to point out the regulatory framework responsible for enabling the compatibility between the current Brazilian teaching model and the assumptions contained in the STS teaching approach. Based on the pedagogical practices covered by the STS movement, we sought to investigate the relationship between science teaching and the traffic education present in Brazilian schools. Finally, the possible connections were developed between some situations that occur in traffic with the physical concepts related to these situations, with the aim of raising student's awareness about the importance of traffic education

O presente trabalho tem por objetivo apontar a possibilidade de se desenvolver, em aulas de física, os conceitos associados à educação para o trânsito, por meio do enfoque CTS. Primeiramente, procurou-se ressaltar como surgiu o movimento CTS, no âmbito global e nacional, e como o ensino de ciências tem sido afetado por essa corrente de pensamento. Em seguida, buscou-se apontar o marco regulatório responsável por viabilizar a compatibilidade entre o atual modelo de ensino brasileiro e os pressupostos contidos na abordagem CTS de ensino. A partir das práticas pedagógicas abarcadas pelo movimento CTS, buscou-se investigar como é a relação entre o ensino de ciências e a educação para o trânsito presente nas escolas brasileiras. Por fim, desenvolveram-se as possíveis articulações entre algumas situações que ocorrem no trânsito com os conceitos físicos relacionados a essas situações, com o intuito de conscientizar os alunos sobre a importância de ser educado para o trânsito
Teaching physics under the CTS approach: relations between the laws of physics and traffic education
Keywords: Física - Estudo e ensino; Trânsito urbano; Educação; Physics Study and teaching